Transportation Network Company (TNC) Ridehailing Travel Patterns in Chicago’s Economically Disconnected Areas - (:unkn) unknown (My University, 2020)
Transportation network companies (TNCs) like Uber and Lyft position themselves as a complement—rather than a detriment—to existing public transportation. Since the launch of TNCs, however, public transit ridership in major cities has steadily declined. This severely impacts economically disconnected residents, who often do not own automobiles and therefore rely on public transportation. The decline of public transit, coupled with the growth of TNCs, thus begs the question: Do TNC services complement or substitute public transportation in serving economically disconnected urban residents? Using data from the American Community Survey and new TNC data from the City of Chicago, this paper maps the destinations of rides originating on Chicago’s Far South Side to analyze travel patterns of low-income individuals. The paper concludes that TNCs are a first mile/last mile solution for the economically disconnected and asks policymakers to improve high-quality transit service and consider public-private partnerships in transit-poor areas.
Keywords: Lyft; Public Transportation; Ridehailing; Transportation Network Company; Uber